Equity in public health standards: a qualitative document analysis of policies from two Canadian provinces - Pinto Andrew D; Manson Heather; Pauly Bernadette; Thanos Joanne; Parks Amanda; Cox Amy (BMC, 2012)
Abstract Introduction Promoting health equity is a key goal of many public health systems. However, little is known about how equity is conceptualized in such systems, particularly as standards of public health practice are established. As part of a larger study examining the renewal of public health in two Canadian provinces, Ontario and British Columbia (BC), we undertook an analysis of relevant public health documents related to equity. The aim of this paper is to discuss how equity is considered within documents that outline standards for public health. Methods A research team consisting of policymakers and academics identified key documents related to the public health renewal process in each province. The documents were analyzed using constant comparative analysis to identify key themes related to the conceptualization and integration of health equity as part of public health renewal in Ontario and BC. Documents were coded inductively with higher levels of abstraction achieved through multiple readings. Sets of questions were developed to guide the analysis throughout the process. Results In both sets of provincial documents health inequities were defined in a similar fashion, as the consequence of unfair or unjust structural conditions. Reducing health inequities was an explicit goal of the public health renewal process. In Ontario, addressing "priority populations" was used as a proxy term for health equity and the focus was on existing programs. In BC, the incorporation of an equity lens enhanced the identification of health inequities, with a particular emphasis on the social determinants of health. In both, priority was given to reducing barriers to public health services and to forming partnerships with other sectors to reduce health inequities. Limits to the accountability of public health to reduce health inequities were identified in both provinces. Conclusion This study contributes to understanding how health equity is conceptualized and incorporated into standards for local public health. As reflected in their policies, both provinces have embraced the importance of reducing health inequities. Both concepualized this process as rooted in structural injustices and the social determinants of health. Differences in the conceptualization of health equity likely reflect contextual influences on the public health renewal processes in each jurisdiction.